GM Science Review Second Report : An open review of the science relevant to GM crops and food based on interest and concerns of the public (Londres GM Science Review Panel, 2004)
Contiene: Section 1: The significance of the Public Debate for the Science Review -- Section 2: New published research -- Section 3: The GM Crop Farm-Scale Evaluations -- Section 4: Feedback on the First Report. Includes Glossary of terms and abbreviations
Keywords: AGRICULTURA